Messua sp. (Salticidae), the host spider of the polysphinctine Inbioia pivai (Ichneumonidae: Pimplinae) - Barrantes Montero, Gilbert (2019)
The koinobiont ectoparasitoids of spiders in the Polysphincta genus group are divided into two well-supported clades. Species in one clade parasitize spiders in the higher araneoid group, and the behaviour of these ectoparasitoids and the parasitized host spiders is relatively well known. On the contrary, wasp species in the other clade parasitize spiders in the RTA group and their behaviour is fragmentary, being known from just a few Palaeartic species. With respect to the latter clade, we report the frst host record for the monotypic genus Inbioia, the salticid Messua. The larva of I. pivai was attached to the posterior edge of the dorsal cephalothorax of Messua. The larva apparently induces the host spider to construct a fnal retreat, much denser than the spider’s typical retreat. In the retreat, the larva kills the spider, sucks out its tissue, and then builds a thin cocoon, tightly attached to the spider retreat.